Patient Reported Outcomes from Portuguese Breast Cancer Patients: Conservative Surgery versus Mastectomy with Immediate Reconstruction. - Pedro José Moreira Maciel (2023)
Background: Despite the numerous advantages of Breast Conserving Treatment (BCT), total mastectomy is still recommended in some patients. When total mastectomy is recommended there are several immediate or delayed breast reconstruction techniques, according to some clinical features and the patient's decision. The aim of this study is to evaluate, through BREAST-Q®, the quality-of-life (QoL) and the satisfaction with the breasts (SWB) in breast cancer patients treated at the Breast Center of the Centro Hospitalar Universitário São João (CHUSJ), according to the type of surgery: BCT or total mastectomy with immediate reconstruction (I-BR). Patients and methods: This is a cross-sectional study, based on survey responses from the patients. The consecutive participants were recruited from the prospectively gathered database of the Breast Center of CHUSJ. Results: Of 365 letters sent, we received 161 answers (44%), and 159 were selected for analysis. Considering the SWB score, no statistical differences were noted. The median Q-score (interquartile range) in the BCT group was 59.00 (16) compared with the I-BR group 57.00 (15), p=0.058; while no significant differences were found for QoL scale between the two surgical groups (I-BR: 71.43 (21) vs BCT: 67.86 (25), p=0.493). We verified that a higher BMI is associated to lower QoL Q-score (p=0.020). Conclusions: BCT provides very good levels of SWB and of QoL. In terms of QoL and SWB there was no statistically significant differences between both groups. Obesity is associated with impaired levels of QoL.